Do toxic metals and trace elements have a role in the pathogenesis of conotruncal heart malformations?. (18th October 2016) - Kundak, Afsin A.; Pektas, Ayhan; Zenciroglu, Aysegul; Ozdemir, Semra; Barutcu, Umit B.; Orun, Utku A.; Okumus, Nurullah
Abstract: Objective: The aim of the present study was to determine the role of toxic elements and trace elements in the pathogenesis of conotruncal heart defects by measuring their concentrations in the first meconium specimens of the affected newborns. Methods: Concentrations of lead, cadmium, iron, zinc, and copper were measured in 1st-day meconium specimens that were collected from 60 newborns with conotruncal heart defects (Group I) and 72 healthy newborns (Group II). Results: The newborns with conotruncal defects and the healthy newborns had statistically similar demographic and clinical characteristics. When compared with healthy newborns, mean concentrations of lead, cadmium, iron, zinc, and copper were significantly higher in newborns with conotruncal heart defects (p=0.001 for each). In total, 51 newborns with conotruncal heart defects had normal karyotype. These newborns had significantly higher concentrations of lead, cadmium, iron, zinc, and copper when compared with healthy newborns. There were significant and positive correlations between the concentrations of lead and cadmium (r=0.618, p=0.001), lead and iron (r=0.368, p=0.001), lead and zinc (r=0.245, p=0.005), lead and copper (r=0.291, p=0.001), cadmium and iron (r=0.485, p=0.001), cadmium and zinc (r=0.386, p=0.001), and cadmium and copper (r=0.329, p=0.001). Conclusion: Toxic metals and trace elements may disturb DNA repair mechanisms by impairing DNA methylation profiles, and thus have a role in the pathogenesis of conotruncal heart defects.